Soul of the Documentary. Framing, Expression, Ethics - Hongisto, Ilona (Amsterdam University Press, 2015)
'Soul of the Documentary' offers a groundbreaking new approach to documentary cinema. Ilona Hongisto stirs current thinking by suggesting that the work of documentary films is not reducible to representing what already exists. By close-reading a diverse body of films - from 'The Last Bolshevik' to 'Grey Gardens' - Hongisto shows how documentary cinema intervenes in the real by framing it and creatively contributes to its perpetual unfolding. The emphasis on framing brings new urgency to the documentary tradition and its objectives, and provokes significant novel possibilities for thinking about the documentary's ethical and political potentials in the contemporary world.